PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN ULAR TANGGA MATERI OPERASI HITUNG PECAHAN KELAS V SEKOLAH DASAR NEGERI 24 CAKRANEGARA TAHUN PELAJARAN 2017/2018 - Aziz, Lalu Abdul (Universitas Pendidikan Mandalika (UNDIKMA), 2018)
This study aims to develop a valid and effective teaching material on grade V Mathematics subjects in elementary school and to find out the results of the development of snake ladder game media in fractional counting operations in class V students. namely the Define, Design, and Develop stages adopted from the FourD Thiagarajan model. The formulation of the problem in this study is how to develop a valid and effective snake ladder game learning media on math subjects operating material to calculate the V class fractions of elementary school in academic year 2017/2018. The results showed that the quality of the snake ladder game media in mathematics learning for elementary school students in grade V was included in the good category, with an average score of material aspects 68.2, from the media aspect 72.25, from a scale of 1-5. The results of the distribution of motivation questionnaires conducted in the field trials with a total of 17 students amounted to 98.42%. This means that the game of the snake game shows that the use of this snake game media has a good impact on improving the learning motivation of fifth grade students at SDN 24 Cakranegara.